KONFIGURASI POLITIK LEGISLASI JAMINAN PRODUK HALAL PERSPEKTIF FIQH SIYASAH - Widyawati, Widyawati (Asy-Syari’ah, 2022)
Abstract: Act Number 33/2024 on Halal Product Guarantee was already issued by the Indonesian government in 2014. The main objective of this act is to ensure comfort, security, safety, and certainty of halal product availability for society in consuming and using products. However, the issues and debates around this bill have drawn severe attention from different parties, especially during deliberation as represented in political configuration. As it was known, political configuration constitutes legal drafting and its implementation as represented in the character and orientation of legal development. This paper concludes that political configuration in the legislation of halal product guarantee is democratic because it was conducted openly and gives room for public participation as well as legislative and executive bodies according to their function proportionally. This political configuration is in line with such principles found inÂ fiqh siyasahÂ as consultation (musyawarah), freedom (hurriyyah) and equality (musawah). This conclusion was drawn using primary and secondary data through the content analysis method. Primary data include official documents related to the bill and act of halal product guarantee, while secondary data refer to articles and books on halal product guarantee. Abstrak: Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal telah disahkan oleh DPR pada 2014 dan diundangkan oleh Presiden pada tahun yang sama. Sesuai dengan tujuannya, undang-undang ini menjamin kenyamanan, keamanan, keselamatan dan kepastian ketersediaan produk halal bagi masyarakat dalam mengonsumsi dan menggunakan produk. Meskipun demikian, isu dan perdebatan seputar RUU ini telah mendapat atensi dari berbagai pihak, terutama dalam pembahasan, sebagaimana tercermin dalam konfigurasi politik. Seperti dimaklumi, konfigurasi politik merupakan proses pembuatan dan pelaksanaan hukum yang tercermin dalam karakter dan arah pembangunan hukum. Tulisan ini berkesimpulan bahwa konfigurasi politik dalam legislasi jaminan produk halal bersifat demokratis, sebab dilakukan secara terbuka dan membuka ruang bagi partisipasi publik dan pihak-pihak legislatif dan pemerintah sesuai fungsinya secara proporsional. Ini sejalan dengan prinsip-prinsip fiqh siyasah yang menekankan musyawarah (syura), kebebasan (hurriyyah),Â dan persamaan (musawah). Kesimpulan itu ditarik dengan menggunakan analisis isi (content analysis), dengan menggunakan data primer dan sekunder. Yang pertama meliputi dokumen-dokumen resmi terkait dengan RUU dan UU JPH, sedangkan yang kedua merujuk pada tulisan-tulisan terkait dengan jaminan produk halal.